Joint position-based impedance control with load compensation for robot arm. (2nd April 2016) - Chiu, Shih-Hsuan; Chen, Cheng-Chin; Chen, Kun-Ting; Huang, Xin-Jie; Pong, Sheng-Hong
Abstract: As part of compliant motion control for a robot arm, the force sensor is usually installed at the wrist of the robot arm to measure the force/moment caused by the external force and the load (the end-effector and the extra object). The robot arm will fail to achieve the desired compliance if the effect of the load is not considered. In this study, a strategy of joint position-based impedance control with load compensation method for the robot arm is proposed, even if the load is unknown. It will distinguish between the external force and the gravitational effect of the load in compliant motion control. Experimental results show that the proposed control method can successfully remove the effect caused by the load, and the robot arm performs compliant motion correctly, in accordance with the impedance characteristic.